2005
DOI: 10.1074/jbc.m508272200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Glutamate-Cysteine Ligase Extends Life Span in Drosophila melanogaster

Abstract: The hypothesis that overexpression of glutamate-cysteine ligase (GCL), which catalyzes the rate-limiting reaction in de novo glutathione biosynthesis, could extend life span was tested in the fruit fly, Drosophila melanogaster. The GAL4-UAS binary transgenic system was used to generate flies overexpressing either the catalytic (GCLc) or modulatory (GCLm) subunit of this enzyme, in a global or neuronally targeted pattern. The GCL protein content of the central nervous system was elevated dramatically in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
131
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 26 publications
11
131
0
1
Order By: Relevance
“…Thus, a higher GSH content in DCAexposed flies might be a consequence of its de novo synthesis stimulated by the elevated expression of gclc and gclm, which is in agreement with earlier studies wherein DCA-induced upregulation of GSH via induction of GCL was observed in mice (Theodoratos et al 2012). Parallel to the above discussion, overexpression of gclc and gclm was reported to extend life span of Drosophila (Orr et al 2005) and de novo synthesis of GSH was also reported against long-term low-dose Îł-irradiation in mice (Lee et al 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, a higher GSH content in DCAexposed flies might be a consequence of its de novo synthesis stimulated by the elevated expression of gclc and gclm, which is in agreement with earlier studies wherein DCA-induced upregulation of GSH via induction of GCL was observed in mice (Theodoratos et al 2012). Parallel to the above discussion, overexpression of gclc and gclm was reported to extend life span of Drosophila (Orr et al 2005) and de novo synthesis of GSH was also reported against long-term low-dose Îł-irradiation in mice (Lee et al 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Another gene was Gclm , which codes for the modulatory subunit of glutamate–cysteine ligase (GCL), the rate‐limiting enzyme in de novo glutathione biosynthesis. Global overexpression of GCLm in flies extended the mean lifespan by 24%, and neuronal overexpression of the catalytic subunit (GCLc) increased mean and maximum lifespans by up to 50% (Orr et al., 2005). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the role of oxidative stress resistance in aging is controversial, and the data presented here may provide new avenues for determining whether there is a causal link between the two (28,29). Irrespective of the role of oxidative stress resistance in aging, alterations in redox homeostasis alone can impact cell-signaling pathways in many ways (30,31).…”
Section: Discussionmentioning
confidence: 99%